Sand failure mechanism and sanding parameters in Niger Delta oil reservoirs (2010)
Sand production is a major issue during oil and gas production from unconsolidated reservoirs. In predicting the onset of sand production, it is important to accurately determine the failure mechanism and the contributing parameters. The aim of this study was to determine sand failure mechanism in the Niger-Delta, identify the major contributing parameters and evaluate their effects on sanding. Completion and production data from 78 strings completed on 22 reservoirs in a Niger Delta oil Field were evaluated. Sand failure mechanisms and contributing parameters were identified and compared with published profiles. The results showed that cohesive stress is the predominant sand failure mechanism. Water cut, Bean size and gas oil ratio (GOR) impact sand production in the Niger Delta.